Pengaruh Likuiditas, Profitabilitas dan Ukuran Perusahaan Terhadap Kebijakan Hutang Pada Perusahaan Syariah Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2021 - wila, Wila Aulia Putri; A. A Miftah; Lidya Anggraeni (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to find out empirical evidence about the effect of Liquidity, Profitability and Firm Size on debt policy. The independent variables in this study are Liquidity, Profitability and Company Size, while the dependent variable is Debt Policy. This type of research is quantitative research. The object in this study is a health sector Islamic company listed on the Indonesia Stock Exchange (IDX) in 2018-2021. The sampling method in this study is the purposive sampling method. The number of companies that were sampled in this study were 17 companies. The data used in this study is secondary data in the form of financial statements. The statistical method uses multiple linear regression analysis, t test, f test and analysis of the coefficient of determination. The results of this study indicate that the t-test of the liquidity variable has an effect on debt policy. Profitability variable has no effect on debt policy, firm size variable has no effect on debt policy. In this study, the F test (simultaneous test) obtained the results that the independent variables had a simultaneous (simultaneous) effect on debt policy. The result of the coefficient of determination shows 0.255 or 25.5%. The results of this coefficient of determination indicate that the ability of the independent variable to explain the dependent variable is 25.5%, the remaining 74.5% is influenced by other factors that can affect debt policy. Keywords: Liquidity, Profitability, Firm Size, debt policy